Influence of physical aspects and throwing velocity in opposition situations in top-elite and elite female handball players - Ferragut, C.; Vila, H.; Abraldes, J. A.; Manchado, C. (Journal of Human Kinetics, 2018)
The relationship between anthropometric and physical characteristics of female handball players and throwing velocity is considered an important factor in handball performance. The aim of this study was to examine key differences in anthropometric and fitness characteristics between top elite and elite female players competing in the first Spanish handball league. A total of 89 players from the first Spanish handball league were divided into two groups, top elite (38) and elite (51) players, and assessed for anthropometric and fitness characteristics (throwing velocity, vertical jump and hand grip strength). A Student`s t-test was used to determine whether a statistically significant difference between the two different levels of play occurred. Significant differences were found in age, body height, body mass, arm span, muscle mass, different girths (tensed and flexed arm, forearm, wrist, ankle), dominant hand width and length, different breadths (biacromial, bitrochanteric, bistyloid breadth and biepicondylar humerus) and fitness characteristics (hand grip strength and throwing velocity for different positions). Top elite players compared to elite players showed differences in anthropometric characteristics which were mainly located in the upper limbs and mostly were nonmodifiable aspects by training. Furthermore, the best players were able to maintain a high throwing velocity in different tactical situations.